Auditoria bajo un ambiente informático a los sistemas económicos automatizados en la Universidad De Granma y en la empresa de conservas de vegetales Granma. su influencia en la calidad - Salazar Ormaza., Rosa Alexandra (2010)
This work was done in the company of canned vegetables Granma, located in the municipality of Manzanillo, Granma Province and the University of Granma, fundamental aims to make a Quality Management Audit, with the aim of eradicating the lack of effectiveness of these systems in the enterprise and otherwise perform an audit of the Automated System of Economic Management at the University, using the Information Technology and Communication within a computer environment. For this purpose, methods and materials applied scientific and economic under the principles of dialectical materialism, as well as bibliographies of authors well known in the industry for quality audit and computer audit. After completion of this research and as a result of Quality Auditing in the entity came to realize that the Canned Vegetables Company meets certain disagreements in the field of quality control, focusing on economic performance and thus their profits.